Improvement of Glycemic Control in Subjects With Poorly Controlled Type 2 Diabetes: Comparison of two treatment algorithms using insulin glargine - Davies, Melanie; Storms, Fred; Shutler, Simon; Bianchi-Biscay, Monique; Gomis, Ramon (Diabetes care, 2005)
OBJECTIVE:--Large prospective studies have demonstrated that optimum glycemic control is not routinely achieved in clinical practice. Barriers to optimal insulin therapy include hypoglycemia, weight gain, and suboptimal initiation and dose titration. This study compared two treatment algorithms for insulin glargine initiation and titration: algorithm 1 (investigator led) versus algorithm 2 (performed by study subjects). RESEARCH DESIGN AND METHODS--A prospective, multicenter (n = 611), multinational (n = 59), open-label, 24-week randomized trial in 4,961 (algorithm 1, n = 2,493; algorithm 2, n = 2,468) suboptimally controlled type 2 diabetic subjects. RESULTS:--At baseline, mean diabetes duration was 12.3 ± 7.2 years, and 72% of subjects were pretreated with insulin. At end point, there was no significant difference in the incidence of severe hypoglycemia between algorithms 1 and 2 (0.9 vs. 1.1%). There was a significant reduction in HbA[subscript 1c] from 8.9 ± 1.3 to 7.8 ± 1.2%, with a greater decrease (P < 0.001) with algorithm 2 (-1.22%) versus algorithm 1 (-1.08%). Fasting blood glucose decreased from 170 to 110 mg/dl, with a greater decrease (P < 0.001) with algorithm 2 (-62 mg/dl) versus algorithm 1 (-57 mg/dl). Mean basal insulin dose increased from 22.9 ± 15.5 to 43.0 ± 25.5 IU, with a significant difference (P < 0.003) between algorithm 2 (21.6 IU) and algorithm 1 (18.7 IU). CONCLUSIONS:--Glargine is safe and effective in improving glycemic control in a large, diverse population with longstanding type 2 diabetes. A simple subject-administered titration algorithm conferred significantly improved glycemic control with a low incidence of severe hypoglycemia compared with physician-managed titration.